Simplifying the Expression: (m+2)(m+1)(3m+5)(95m)
This article will guide you through simplifying the expression (m+2)(m+1)(3m+5)(95m).
Step 1: Expanding the Products
We begin by expanding the products using the distributive property (also known as FOIL method):

(m+2)(m+1) = m(m+1) + 2(m+1) = m² + m + 2m + 2 = m² + 3m + 2

(3m+5)(95m) = 3m(95m) + 5(95m) = 27m  15m² + 45  25m = 15m² + 2m + 45
Step 2: Combining Like Terms
Now we substitute the expanded products back into the original expression:
(m+2)(m+1)(3m+5)(95m) = (m² + 3m + 2)  (15m² + 2m + 45)
Next, we remove the parentheses by distributing the negative sign:
= m² + 3m + 2 + 15m²  2m  45
Finally, we combine the like terms:
= 16m² + m  43
Conclusion
Therefore, the simplified form of the expression (m+2)(m+1)(3m+5)(95m) is 16m² + m  43.